Odpowiedzi

  • Użytkownik Zadane
2013-07-11T16:04:02+02:00

x1 + x2 = 2

x1² + x2² = 16

 

x1² + x2² = 16

(x1 + x2)² - 2x1x2 = 16

2² - 2x1x2 = 16

-2x1x2 = 16 - 4

-2x1x2 = 12

x1 * x2 = - 6

 

x1 + x2 = 2

x1 * x2 = -6

 

-b/a = 2

c/a = -6

 

-b = 2a

c = -6a

 

b = -2a

c = -6a

 

ax² + bx + c = 0

dla np a = 1 otrzymujemy

b = -2 * 1 = -2    

c = -6 * 1 = -6 

czyli otrzymujemy równanie:

x² - 2x - 6 = 0     -------  odpowiedź

 

spr.

x² - 2x - 6 = 0

Δ = (-2)² - 4 * 1 * (-6) = 4 + 24 = 28

√Δ = √28 = 2√7

x1 = (2 - 2√7)/2 = 1 - √7

x2 = (2 + 2√7)/2 = 1 + √7

 

x1 + x2 = 1 - √7 + 1 + √7 = 2         tyle miała wyjść suma pierwiastków x1 i x2

x1² + x2² = (1 - √7)² + (1 + √7)² = 1 - 2√7 + 7 + 1 + 2√7 + 7 = 16  czyli też dobrze wyszło

1 5 1